High Risk of Surgical Glove Perforation From Surgical Rotatory Instruments. Issue 11 (November 2016) - Goldman, Ashton H.; Haug, Emanuel; Owen, John R.; Wayne, Jennifer S.; Golladay, Gregory J.
Abstract: Background: Surgical gloves can be damaged during the course of a procedure, which can place the surgeon and patient at risk. Glove perforation may not always be readily apparent, and determining the risk factors for glove perforation can aid the surgeon in deciding when a glove change is advisable. Time of wear and needle sticks have been well studied; however, other mechanisms including mechanical stress from surgical equipment have had limited evaluation to date. Questions/purposes: We evaluated the risk of glove perforation in gloves that were caught in a surgical rotatory device (such as drills and reamers). The aims of our study were (1) to determine the percentage of undetected microperforations after entanglement on a rotatory tool during orthopaedic procedures, (2) to determine which kinds of rotatory devices most commonly cause such microperforations, and (3) to assess whether time of wear had an effect on the risk of perforation. Methods: From July 2014 to September 2015, 33 gloves were obtained from all orthopaedic subspecialties at our Level I trauma center if they were caught in a rotatory device greater than one revolution. Time of glove wear and location of the glove that was caught in a rotatory device were recorded. After an evaluation for macroperforations (≥ 5 mm), the gloves were evaluated for microperforations (< 5 mm) via the American Society for Testing and Materials (ASTM) one‐liter load test. Time of wear was compared among gloves with macroperforations, microperforations, and no perforations. Results: The 33 gloves obtained came from 33 procedures. Seventeen of 33 (52 %) gloves had perforations. Seven of the 17 perforated gloves had macroperforations while 10 had microperforations. Eleven of 33 entanglements were caught by drills, nine by reamers, eight by K‐wires, and the remaining five gloves were caught by various other instruments. Eight of 17 perforations were caused by drills, three by reamers, three by K‐wires, and three by various other instruments. The average time of wear was 58 minutes which did not differ with pattern of glove damage. Conclusion: Surgical gloves caught in a rotatory power instrument are likely to have been perforated, regardless of the amount of time that they had been worn. Visual inspection appears to be an inadequate test of glove integrity. When a glove becomes entangled in a rotary instrument such as a drill, pin, or reamer, a surgeon should change the gloves regardless of whether he or she believes a perforation is present. Level of Evidence: Level IV, therapeutic study.